UMP TRIZ produced 150 innovative projects - UMP, PNC (2019)
A total of 150 innovative projects were produced in UMP TRIZ Programme, Innovation Exposition 3.0, involving 866 Universiti Malaysia Pahang (UMP) students that was held at the Sports Complex, UMP Gambang Campus on December 16, 2018.